Adenoid basal carcinoma of the cervix uteri - Shilkin, K. B. (1972)
This paper describes a case of adenoid basal carcinoma of the uterine cervix, occurring in a woman aged 78 years. In view of the rarity and the limited knowledge of this group of neoplasms, details of the clinical history, the histological appearances, and the histochemical reactions are presented. An attempt is made to define the histogenesis of the tumour and some points on nonmenclature are discussed. It is suggested that the tumour arises from multipotential cervical basal cells and that the adenoid structures rather than being true glands are formed by degeneration of the connective tissue stroma. On the basis of a review of reported cases it seems possible that this tumour will be shown to be one of low-grade malignancy.